PENGARUH MOTIVASI, DISIPLIN DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN CV. HARMONY GEMILANG - Aqili, Willy; Solehudin, Solehudin (Faculty of economcs Universitas Singaperbangsa Karawang, 2023)
This study aims to examine and analyze the influence of motivation, discipline and work environment on employee performance of Cv. Harmony Gemilang. This research was conducted using quantitative methods with descriptive and verification analysis, namely collecting, presenting, analyzing, and testing hypotheses, as well as making conclusions and suggestions. The sample in this study amounted to 108 using the Non Probability Sampling technique with the Saturated Sample method. Based on the analysis that has been done this research proves that Employee Motivation in Cv. Harmony Gemilang is good, Employee Discipline at Cv. Harmony Gemilang is quite good, Employee Work Environment at Cv. Harmony Gemilang is good and Employee Performance at Cv. Harmony Gemilang is already good. The correlation coefficient between the variables of Motivation, Discipline and Work Environment has a strong, positive and significant correlation level. The influence of the work environment variable coefficient contributes to performance more than motivation and discipline. The simultaneous influence of work motivation, discipline and work environment on employee performance is 67.1% while the remaining 32.9% is the contribution of other variables not examined.